2004
DOI: 10.1038/sj.bjc.6601705
|View full text |Cite
|
Sign up to set email alerts
|

Role of infiltrated leucocytes in tumour growth and spread

Abstract: Leucocytes are a major component of the tumour microenvironment. Recent studies have indicated that the infiltration and activity of these host cells are regulated by the tumour to promote its survival and progression. Through the production of an array of growth factors, proteases and angiogenic mediators, leucocytes in the tumour microenvironment promote tumour growth, angiogenesis and metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
204
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 254 publications
(211 citation statements)
references
References 72 publications
6
204
0
1
Order By: Relevance
“…26 This phagocyte class exerts a number of biological actions in common with neutrophils that may explain this prognostic value. 8 In this study no association was found between the peripheral lymphocyte count and outcome following CLM resection, even when further analyses were conducted to evaluate multiple cut-off points (data not shown).…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…26 This phagocyte class exerts a number of biological actions in common with neutrophils that may explain this prognostic value. 8 In this study no association was found between the peripheral lymphocyte count and outcome following CLM resection, even when further analyses were conducted to evaluate multiple cut-off points (data not shown).…”
Section: Discussionmentioning
confidence: 56%
“…23,39 Whilst it is possible that increasing neutrophil count is simply an epiphenomenon of the inflammatory response in the vicinity of the tumour, the emerging theory of 'immune enhancement' suggests that cells of the myeloid lineage, particularly neutrophils, are recruited from the circulation and play a direct role in promoting aggressive tumour phenotypes. 8,9 Neutrophils are the major producers of a number of ligands that may induce tumour cell proliferation and invasion, including transforming growth factor-. 43 Furthermore, granulocytes, particularly neutrophils, contain over two-thirds of circulating vascular endothelial growth factor, liberation of which may promote tumour vascularisation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations